Courageous faith : my story from a life of obedience - Stanley, Charles F. (New York : Howard Books, an imprint of Simon & Schuster, Inc., 2016)
In this book from Dr. Charles Stanley, he looks his readers in the eye and says, This is how my faith has worked for me at the most challenging times of my life and how it has led me to the victories God had in store for me. As Dr. Stanley looks back over his long life of ministry, he is now ready to share how his personal faith choices directed his every step. He shares how God walked with him through his most difficult days as a pastor when he faced internal conflict in a church he'd led for years. He gently shares painful family issues that brought him to his knees and taught him to look to God for answers when life wasn't simple and trite answers didn't work. Dr. Stanley reminds us that choosing to follow and obey God when life is hard can be both the toughest and best thing we'll ever do. As Dr. Stanley reflects on the biblical teachings that have led him through his difficulties and joys, he always comes back to this principle: Do what God says is right and leave the consequences to Him -- no matter what that means.
Beginnings -- Finding purpose -- Foundational influences -- Unexpected intervention -- Fields of service -- Battles -- Struggling with loss -- Until the day of Christ Jesus.
Includes bibliographical references.
Keywords: Stanley, Charles F; Baptists -- Georgia -- Atlanta -- Clergy -- Biography; Religion -- Christian Life -- Inspirational; Religion -- Christian Life -- Spiritual Growth; SELF-HELP -- Personal Growth -- Happiness